STRATEGI PEMASARAN BERAS DALAM PENINGKATAN PENJUALAN DI CV BANGKIT JAYA BELIREJO KECAMATAN BELITANG II KABUPATAN OKU TIMUR - Setiyo Putri, Krisitin; Feriyana, Winda (Jurnal Trisna Riset, 2024)
Rice is one of the basic needs of Indonesian people. Rice farmers provide employment and a source of income for millions of agricultural households. CV Bangkit Jaya Rice Factory is a business institution engaged in rice production. The aim of this research is to analyze the rice marketing strategy implemented by CV Bangkit Jaya to increase sales. The research method used is a quantitative descriptive approach with data collection techniques through field research (Field Research) and library research (Library Research). The results of the discussion obtained a linear regression equation, namely 104400 11000x, so that in 2024 it can be predicted to be 148800 Kg. in 2025 it will be 159400 Kg, in 2026 it will be 170400 Kg, the standard error obtained is SE 1187 Kg. From the calculation results, the research results show that the marketing strategy implemented includes market segmentation, competitive pricing, wide distribution, and promotion through social media and partnership networks. With this strategy, CV Bangkit Jaya has succeeded in increasing the competitiveness of its products in the local market. However, there are several challenges, such as fluctuating raw material prices and intense market competition. Therefore, this research recommends optimizing digital marketing strategies and improving customer service quality in order to maintain and increase the company's market share.